El concepto y el tratamiento del bloqueo biológico en las infecciones agudas - Gret, Luis G. (1937)
The germs or the toxins introduced into the organism are decomposed (peptonized) in two orders of substances : lisinas (toxic) and haptinas (curative). The lisinas are fixed in the cells, provoking sero-leukocytic exudation and cellular edema, which originate the anatomical blockade. In the periphery of this zone another structural blockade is formed due to the hidropic state of the cells. From this results the isolation of the focus from the rest of the organism, regarding the interchange of tissue reactions. It is due to this, that the curative substances, Haptinas or Antibodies do not reach the site of the lesion, or it is done insufficiently. Thus causing the malnutrition of the cells, their death, and the formation of toxic necrolisinas. The encystemcnts of medicinal substances is also due to the same blockade. The treatment which is instituted must : 1st Cure the blockade through decompression of the focus, be it by evacuating punctions, or by intravenous injections of hypertonic sodium chloride. 2nd To avoid the irritation of the endings of the nerves through anaesthesia of the same. 3rd To favour the production of Haptinas by Haptindgcno which is injected in situ if there is blockade, and subcutaneously if there is none. 4th To dilute the Caustic and to avoid the nervous irritations in cases of encystment of medicinal substances, through injections of solution of physiological salt and anaesthetic.